Shared early molecular mechanisms revealed in P301S and 5xFAD Alzheimer’s disease mouse models - Huda Suloh; Shashank Kumar Ojha; Maryam Kartawy; Wajeha Hamoudi; Manish Kumar Tripathi; Wisam Bazbaz; Nofar Schottlender; Uri Ashery; Igor Khaliulin; Haitham Amal (Translational Psychiatry)
Abstract Alzheimer’s disease (AD) is the most common neurodegenerative disorder characterized by early molecular events that influence disease progression. Still, the molecular mechanisms caused by different mutations of AD are not understood. We have performed a multidisciplinary study to investigate and compare the early stages of the pathology in two transgenic AD mouse models: P301S and 5xFAD. Using SNOTRAP-based mass spectrometry, we assessed changes in S-nitrosylation, a nitric oxide-mediated post-translational modification, of proteins in both models during their juvenile age. The increased levels of 3-nitrotyrosine confirmed nitrosative stress in the mutant mice. Systems biology analysis revealed shared processes between the models, particularly in the γ-aminobutyric acid (GABA)ergic and glutamatergic neurotransmission processes. In the P301S model, we identified 273 S-nitrosylated (SNOed) proteins in the cortex, with 244 proteins uniquely SNOed in the diseased mice. In the 5xFAD model, 309 SNOed proteins were identified. We have found altered proteins expression of different glutamate/GABA-related markers in the cortex and hippocampus of both AD mouse models. Additionally, the phosphorylation levels of the mTOR signaling components revealed hyperactivation of this pathway in P301S mice. Conversely, 5xFAD mice showed no significant changes in mTOR signaling except for elevated phosphorylation of the ribosomal protein S6 in the cortex. Our findings revealed key molecular mechanisms in the two AD mouse models during their early stages. These mechanisms could serve as potential biomarkers and therapeutic targets for early-stage AD.